Resonant Ion Beam Interaction with Whistler Waves in A Magnetized Dusty Plasma (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
The theory of whistler wave interaction with an ion beam injected parallel to the magnetic field in an unbounded plasma is considered. The excited whistler waves propagate parallel to the beam direction and their phase velocity is a characteristic of beam-whistler resonant cyclotron coupling. The frequency and the growth rate of the unstable wave increase with the relative density of negatively charged dust grains. The ion beam velocity responsible for maximum growth rate increases as the charge density carried by dust increases. The maximum value of growth rate increases with the beam density and is proportional to the square root of beam density. These results should shed light on mechanisms of whistler wave excitation in space plasmas by artificial beams injected from spacecraft in the ionosphere and the magnetosphere.
Keywords: 52